Our experience of the de la torre-mondragon technique in the surgical management of hirschsprung's disease: A report on 52 cases - Mouafo Tambo Faustin Félicien; Gacelle Fossi Kamga; Eugénie Caroline Dikongue Dikongue; Florence Obono Ebo; Maurice Aurélien Sosso (Wolters Kluwer Medknow Publications, 2024)
Background: The authors report their experience of the transanal endorectal pull through technique as described by De la Torre Mondragon in the treatment of Hirschsprung's disease (HD). Materials and Methods: It was a retro prospective, observational and descriptive hospital based study involving all proven cases of HD managed within a time frame of 8 years. Results: Fifty two patients with a mean age of 18 months at the time of surgery. The male pre dominance was remarkable. The mean duration of the surgery was 2 h and a half hours. The surgical indication was based on the history, clinical findings and on the contrast enema (transition zone) with a 24 h film (prolonged contrast evacuation) and calculation of the rectosigmoid index (<1). With a mean follow up of 16 months, the morbidity was dominated by soiling, anastomotic strictures and enterocolitis. The mortality in one case was related to a post operative enterocolitis that was not amenable to resuscitation. Conclusion: Soiling, anastomotic strictures and enterocolitis are the main post operative complications of TEPT in the treatment of HD in our practice.